Plerixafor induces the rapid and transient release of stromal cell-derived factor-1 alpha from human mesenchymal stromal cells and influences the migration behavior of human hematopoietic progenitor cells - Wuchter, Patrick; Leinweber, Christina; Saffrich, Rainer; Hanke, Maximilian; Eckstein, Volker; Ho, Anthony Dick; Grunze, Michael; Rosenhahn, Axel (Cell & tissue research, 2014)
The interaction between the stromal cell-derived factor-1 alpha (SDF-1α, CXCL12) and its chemokine receptor CXCR4 has been reported to regulate stem cell migration, mobilization and homing. The CXCR4 antagonist plerixafor is highly efficient in mobilizing hematopoietic progenitor cells (HPCs). However, the precise regulatory mechanisms governing the CXCR4/SDF-1α axis between the bone marrow niche and HPCs remain unclear. In this study, we quantify the impact of plerixafor on the interaction between human bone marrow derived mesenchymal stromal cells (MSCs) and human CD34+ HPCs. An assessment of SDF-1α levels in the supernatant of MSC cultures revealed that exposure to plerixafor led to a transient increase but had no long-term effect. In Transwell experiments, we observed that the addition of SDF-1α significantly stimulated HPC migration; this stimulation was almost completely antagonized by the addition of plerixafor, confirming the direct impact of the CXCR4/SDF-1α interaction on the migration capacity of HPCs. We also developed a new microstructural niche model to determine the chemotactic sensitivity of HPCs. Time-lapse microscopy demonstrated that HPCs migrated actively along an SDF-1α gradient within the microchannels and the quantitative assessment of the required minimum gradient initiating this chemotaxis revealed a surprisingly high sensitivity of HPCs. These data demonstrate the fine-tuned balance of the CXCR4/SDF-1α axis and the synergistic effects of plerixafor on HPCs and MSCs, which most likely represent the key mechanisms for the consecutive mobilization of HPCs from the bone marrow niche into the circulating blood.